ACCELERATION OF BANK PERKREDITAN RAKYAT'S DIGITAL SERVICES IN BOOSTING FINANCIAL PERFORMANCE: ANALYTICAL PERSPECTIVES OF INDONESIAN RURAL BANK LOANS CUSTOMERS - Muhammad Alfarizi; Ngatindriatun Ngatindriatun (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2022)
Rural Banks (BPR) are the closest microfinance institutions for people who need funding, especially micro-scale businesses. The transformation of digital banking services is an absolute thing that BPRs must implement to win the competitive competition in the Indonesian financial sector. Currently, many rural banks have adopted digital services in their business operations. This study will further investigate customer experience and its relationship with intermediary variables to analyze the impact of digital service transformation on the financial performance of rural banks in Indonesia. Descriptive quantitative research was selected to evaluate the digital services of BPR Indonesia by interpreting the relationship of 11 hypotheses formed from the variables of solving problems of BPR digital services, customer peace of mind, focus on BPR digital service outcomes, product experience, customer experience, Word of Mouth, customer satisfaction, trust customers and BPR's financial performance. This research is a type of explanatory research where the variable relationship testing is done through a quantitative approach to proving the hypothesis with SEM analysis techniques. The results of the study show support for almost all hypotheses except the hypothesis of the effect of Word of Mouth on BPR performance which is explained further. This research has managerial implications for a strategy for digitizing inclusive BPR services and understanding customers and the market. Theoretical implications develop along with the role of academics in doing applied innovation research in strengthening rural credit banks as microfinance institutions for the competitiveness of a developed nation's economy.